Praktik Cyber Religion Remaja Perkotaan - Akhmad Pandhu Wijaya; Agung Nugroho; Mahfudlah Fajrie; M. Nashrul Haqqi; Puja Pratama; Achmad Umar Setyadi; Virasti Setiani; Dwi Fania (Unitri Press, 2023)
The emergence of various models of religion in the cyber era has certainly influenced the religious behavior of teenagers in cities. This research seeks to analyze cyber religion practices carried out by Muslim teenagers in the city, by focusing on the use of social media in their religious practices. This research uses an ethnographic method with the supporting method being virtual ethnography. The informants were Muslim teenagers. Data collection techniques use observation, interviews and documentation. The research results show that the practice of cyber religion has become a routine for teenagers, this is done as a form of seeking religious information or knowledge and deepening Islamic teachings, apart from that the practice of cyber religion is also used as entertainment for some teenagers. The digital platforms that are often used are YouTube and Instagram. These two media are popular with teenagers because they are considered to represent the needs and lives of urban teenagers who are mobile, fast and instant, so that for teenagers the most important thing in religious practice is the media and the information. This is what allows anyone to become a figure (da’i) transmitting religious teachings, and can even cause the death of religious figures. Abstrak Munculnya beragam model keberagamaan di era cyber ini tentunya mempengaruhi perilaku beragama para remaja kota. Penelitian ini berusaha menganalisa praktik cyber religion yang dilakukan remaja muslim di kota, dengan berfokus pada penggunaan media sosial dalam praktik keagamaannya. Penelitian ini menggunakan metode etnografi dengan metode pendukung adalah etnografi virtual. Informannya adalah para remaja muslim. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa praktik cyber religion sudah menjadi rutinitas para remaja, hal tersebut dilakukan sebagai wujud untuk mencari informasi atau pengetahuan agama dan memperdalam ajaran Islam, selain itu praktik cyber religion juga digunakan sebagai hiburan bagi sebagian remaja. Platform digital yang sering digunakan adalah youtube dan instagram. Kedua media tersebut digemari para remaja karena dianggap merepresesntasikan kebutuhan dan kehidupan remaja kota yang mobile, cepat dan instan, sehingga bagi para remaja yang terpenting dalam praktik keagamaan adalah media dan informasinya. Hal inilah yang membuat siapapun bisa menjadi tokoh (da’i) penyampai ajaran agama, bahkan bisa membuat matinya tokoh-tokoh agama.